European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB): An Update on the Pediatric CEUS Registry on Behalf of the "EFSUMB Pediatric CEUS Registry Working Group" - Dietrich, Christoph F.; Augustiniene, Rasa; Batko, Tomasz; Cantisani, Vito; Cekuolis, Andrius; Deganello, Annamaria; Dong, Yi; Franke, Doris; Harkanyi, Zoltan; Humphries, Paul D.; Jedrzejczyk, Maciej; Jüngert, Jörg M.; et al. (Ultraschall in der Medizin, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-04-02